Leading "Around Scripture" - H. Welzen (Acta Theologica)
The article discusses the Carmelite programme “Around Scripture” as a recent development in the Order, in particular the leadership of the programme. It explains the kind of activity “Around Scripture” entails and the best approach to it. It investigates the capabilities a leader needs to guide the sharing within a group, in particular his/her reading competence and exegetical capabilities. Because reflection in “Around Scripture” also relates to spirituality and the spiritual way (both in the Biblical text and in the participants) and because it also concerns processes of appropriating spirituality, the article considers the leader’s knowledge of spirituality and analyses his/her mystagogical capabilities. The article concludes with a brief discussion of the leader’s unselfishness.